Critical Perspective And Reconstruction Governance Organization Management Zakat In Indonesia - Santoso, Cahyo Budi; Alim, Mohammad Nizarul; Riyadi, Slamet (Archives of Business Research, 2018)
BAZNAS ss an official institution and given the authority in the management of zakat in Indonesia, then in order to accountability the management of zakat needs to be based on a variety of regulatory and operational strengthening. Organization Manager Zakat is the organization that manages the funds of the community i.e. the funds to charity. OPZ has the role of intermediation zakat fund convened to the community i.e. muszaki and transmitted and harnessed to the community mustahik. For a regulation related to the management of zakat be very important. This research is qualitative one, with descriptive design. While, data taking was done by observations and deeply interviews. This study used qualitative research method where the data were collected by observation and in-depth interviews. The data collection was done in natural settings. Primary data were collected through participant observation towards staff who received allowances, in-depth interviews and documentation (audio recording). Respondents in this study consist of four informants. Important findings in this research are: (1) Transparent on BAZNAS marked information in a timely, adequate, accessible, business objectives, strategies, financial condition, the company arrangement and compensation of Executive Board, the controlling shareholder, internal control and supervision system, the principle of openness and policy writing and proportionate. (2) Accountability at BAZNAS marked the details of duties and responsibility of the organ and all employees clear, aligned with the vision, mission, values and strategy BAZNAS. employees were able to on duty, responsibility, and its role in the implementation of GCG Principles, tasks and authority, ethical behaviour and employee agreed. (3) Responsibility on BAZNAS in mark awareness of responsible offices attached, awareness of the existence of social responsibility and working in a professional manner and uphold ethics and code of conduct of the organization.(4) Independence at BAZNAS in mark awareness being the responsibility of the appropriate Office attached to, awareness of social responsibility and professional ethics, and code of ethics of the Organization and maintaining a healthy work environment and is conducive and (5) Fairness in BAZNAS in the mark system of payment of Zakah are easy and simple on-line through the medium, the amount of the payment of zakat muzakki is equal to the amount agreed upon in advance and accept criticism and suggestions from other parties.